Konseling Kelompok Realita untuk Meningkatkan Identitas Diri Pengguna Aplikasi TikTok - Gusti Rahayu Neviyarni; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Departement of Mathematics Education, 2023)
The TikTok application is a means of entertainment that makes its users have to be able to fortify themselves from negative influences so they don’t lose their identity. Individual identity as an identity or differentiator between himself and others. Imperfect self-identity will make individuals trapped in situations that can harm themselves and those around them, such as having a feeling of being unable to do something, helplessness, decreased self-esteem, lack of confidence, and so on. Reality group counseling is one of the guidance and counseling services that can help individuals improve their self-identity by utilizing group dynamics in the process of their activities. The method used in this study is descriptive qualitative with a literature study approach which provides a detailed description of reality group counseling to improve self-identity.